One‐year outcomes of an intense workplace cardio‐metabolic risk reduction program among high‐risk employees: The My Unlimited Potential. (6th December 2015) - Rouseff, Maribeth; Aneni, Ehimen C.; Guzman, Henry; Das, Sankalp; Brown, Doris; Osondu, Chukwuemeka U.; Spatz, Erica; Shaffer, Brandon; Santiago‐Charles, Joann; Ochoa, Teresa; Mora, Joseph; Gilliam, Cynthia; et al.
Abstract : Objective: This study details 6‐ and 12‐month cardio‐metabolic outcomes of an intense 12‐week workplace lifestyle intervention program, the My Unlimited Potential (MyUP), conducted in a large healthcare organization. Methods: This study was conducted among 230 employees of Baptist Health South Florida with high cardiovascular disease (CVD) risk. Employees were considered at high risk and eligible for the study if they had two or more of the following cardio‐metabolic risk factors: total cholesterol ≥ 200 mg/dl, systolic blood pressure (SBP) ≥ 140 mmHg or diastolic blood pressure (DBP) ≥ 90 mmHg, hemoglobin A1C (HbA1c) ≥ 6.5%, body mass index (BMI) ≥ 30 kg/m 2 . Results: At the end of 12 weeks, there was significant reduction in the mean BMI, SBP and DBP, serum lipids, and HbA1c among persons with diabetes. At 1 year, there was significant decline in the mean BMI, SBP and DBP, HbA1c, and high‐sensitivity C‐reactive protein, and in the prevalence of poor BP control, BMI ≥ 35 kg/m 2, and abnormal HbA1c among all persons and those with diabetes. Conclusions: This intensive 12‐week lifestyle change program was successful at improving cardio‐metabolic risk factors at 1 year. This study provides a template for other workplace programs aimed at improving CVD risk in high‐risk employees.